2017
DOI: 10.1590/s1517-707620170002.0155
|View full text |Cite
|
Sign up to set email alerts
|

Estudo do processo de lixiviação controlada da escória de aciaria em extrator soxhlet visando emprego em pavimentos

Abstract: RESUMOEste trabalho aborda a caracterização das propriedades físicas, químicas e mecânicas da escória de aciaria para emprego como agregado antes e após ensaio de lixiviação controlada em extrator Soxhlet. O material foi caracterizado antes de passar por processo de estabilização (escória virgem) e após lixiviação controlada em períodos distintos de 24, 56, 96, 120 horas. A escória foi submetida, em laboratório, a uma simulação de precipitação em equipamento Soxhlet visando avaliar suas propriedades físicas, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…It is observed in the range of 293 to 1173 K the sample mass loss was 2.83%, this result is very close to the result found by Machado 10 , whose value is characteristic of magnesium oxide (Mg(OH) 2 ), calcium hydroxide (Ca(OH) 2 ) and calcium and magnesium carbonates (CaCO 3 or MgCO 3 ), indicating that the loss of mass is due to dehydration and decarbonation of these compounds. Figure 4 shows the thermogram of the same sample (lot 02), with an oxidizing atmosphere (synthetic air), after the test of removal of water (H 2 O) and carbon dioxide (CO 2 ) in an inert atmosphere.…”
Section: Chemical Characterization 321 Thermal Analysis (Tga/dta)supporting
confidence: 88%
See 4 more Smart Citations
“…It is observed in the range of 293 to 1173 K the sample mass loss was 2.83%, this result is very close to the result found by Machado 10 , whose value is characteristic of magnesium oxide (Mg(OH) 2 ), calcium hydroxide (Ca(OH) 2 ) and calcium and magnesium carbonates (CaCO 3 or MgCO 3 ), indicating that the loss of mass is due to dehydration and decarbonation of these compounds. Figure 4 shows the thermogram of the same sample (lot 02), with an oxidizing atmosphere (synthetic air), after the test of removal of water (H 2 O) and carbon dioxide (CO 2 ) in an inert atmosphere.…”
Section: Chemical Characterization 321 Thermal Analysis (Tga/dta)supporting
confidence: 88%
“…The most intense peak occurs near 723 K and refers to the decomposition of calcium hydroxide -Ca(OH) 2 releasing water. It is observed that this peak has a small shoulder at a lower temperature, 701 K, which possibly must be correlated to the decomposition of magnesium hydroxide -Mg(OH) 2 . Due to the small amount presented in the thermogram, this compound was not detected in the X-ray diffraction analyzes.…”
Section: Chemical Characterization 321 Thermal Analysis (Tga/dta)mentioning
confidence: 93%
See 3 more Smart Citations